Patient reported outcome measure domains and tools used among adolescents and young adults with cancer: A scoping review. (January 2023) - Engstrom, Teyl; Tanner, Sarah; Lee, Wen Ray; Forbes, Cheryl; Walker, Rick; Bradford, Natalie; Pole, Jason D.
Abstract: Adolescent and young adult (AYA) cancer patients and survivors are growing and face with distinct issues from paediatric and older cancer survivors. Hence it is important the issues they encounter are measured using appropriate Patient Reported Outcome Measures (PROMs). We searched PubMed, EMBASE, CINAHL, and PsycINFO for articles including: (1) AYAs (ages 15–39), (2) Malignant neoplasms, and (3) PROMs. This resulted in 3566 unique articles, 523 were included for full text review, of which 175 were included. These studies included 203 distinct tools to measure PROMs across 31 domains. Physical function was most frequently measured domain, followed by social, emotional and mental health. The most commonly used tools were the EORTC QLQ-C30, HADS and SF-36. PROMs used in AYA cancer patients is a complex topic, this comprehensive review serves as a useful reference for researchers, clinicians and health services who want to better understand, and improve, outcomes among their patients. Graphical Abstract: Adolescent and young adult (AYA) cancer patients and survivors are a growing group with varied and distinct issues from paediatric and older cancer survivors. Hence it is important that the issues facing this group are measured using appropriate Patient Reported Outcome Measures (PROMs). Our review found 175 studies that reported PROMs among AYA cancer patients and survivors. The PROMs included in these studies spanned 31 domains and were measured using 203 different instruments, as shown in the graph. ga1 Highlights: We found 175 studies describing PROMs in AYA cancer patients in the last 10 years. 203 distinct tools were used to measure PROMs across 31 different domains. Physical function, social, emotional and mental health domains were most measured. EORTC QLQ-C30, HADS and SF-36 were the tools most frequently used.